Borders, Violence, Law - De Lucas, Javier (The Age of Human Rights Journal, 2014)
This article explores the relationship between violence, law and borders by analyzing both the violence at the borders and the violence of the borders. In both cases, the author states that violence exerted by means of law, as well as migratory and asylum policies, threaten the universal human rights of the most vulnerable people and cannot be seen as exercising the legitimate monopoly of force, resulting in the destruction of the Rule of Law.